Internet as a Means of Teaching a Foreign Language - Mirzoeva Laylo (European Science Publishing, 2023)
The article considers the Internet as a means of learning. In teaching, a special emphasis is placed today on the child's own activity in search, awareness and processing of new knowledge. The teacher acts as the organizer of the learning process, the leader of the amateur activities of students, providing them with the necessary assistance and support. The Internet as a means of teaching a foreign language is the best way to implement many of the goals and objectives of education and upbringing.
Keywords: Internet, learning, foreign language, education.